1997
DOI: 10.1080/02687039708248475
|View full text |Cite
|
Sign up to set email alerts
|

Proverb interpretation in fluent aphasia and Alzheimer's disease: Implications beyond abstract thinking

Abstract: This study compared proverb processing across three groups, i.e. patients with fluent aphasia (APH), patients with Alzheimer's Disease (AD), and normal control subjects (NC). Proverb stimuli were used to examine the effects of group membership and proverb familiarity in two presentation formats (i.e. spontaneous versus multiple-choice) on performance. The sensitivity of linguistic and cognitive measures as predictors of ability to interpret proverbs was also investigated. In relation to NC subjects, patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 12 publications
0
23
0
2
Order By: Relevance
“…Given the sensitivity of a PI task to declines in abstract verbal reasoning (Van Lancker, 1990) and figurative language processing, we elected to use a proverb interpretation task as one of our discourse outcome measures. Chapman et al (1997) compared persons with fluent aphasia, persons with AD and healthy elders on their ability to interpret familiar and unfamiliar proverbs. They found that persons with AD performed well on interpretation of familiar proverbs but had difficulty with unfamiliar proverbs.…”
Section: Proverb Interpretationmentioning
confidence: 99%
See 3 more Smart Citations
“…Given the sensitivity of a PI task to declines in abstract verbal reasoning (Van Lancker, 1990) and figurative language processing, we elected to use a proverb interpretation task as one of our discourse outcome measures. Chapman et al (1997) compared persons with fluent aphasia, persons with AD and healthy elders on their ability to interpret familiar and unfamiliar proverbs. They found that persons with AD performed well on interpretation of familiar proverbs but had difficulty with unfamiliar proverbs.…”
Section: Proverb Interpretationmentioning
confidence: 99%
“…The highest possible score on the test was 30 (5 items  6 points). To ensure reliability of scoring, baseline and first year postintervention transcripts were scored by Chapman and colleagues, using their guidelines (Chapman et al, 1997). At the end of the first year, the second author scored all patient responses, following Chapman's guidelines and consulting with her on questionable responses.…”
Section: Discourse Outcome Measuresmentioning
confidence: 99%
See 2 more Smart Citations
“…AD patients failed to correspond the meaning of the idiomatic phrase with a relevant picture or a one-word description; they understood the phraseme literally / by semantic associations to words from the idiom without processing sentential meaning (Rassiga, Lucchelli, Crippa, & Papagno, 2009, p. 409). The patients also manifested significant problems selecting the correct abstract word to explain even familiar proverbs (Chapman, Ulatowska, Franklin, Shobe, Thompson, & McIntire, 1997). Since AD damages the cortex, the patients are impaired in different cognitive domains; they lose the ability to grasp the idiom holistically on the ground of their own communicative and cognitive experience when they performed the tests.…”
mentioning
confidence: 99%